Writ on water - Jackson, Melanie (New York, NY. : Donchester., 2007)
Unable to make sense of her visions, photographer Chloe, while on assignment in Virgina, is plagued by terrifiying dreams of murder and soon discovers that there is no one she can trust.
Keywords: Precognition -- Fiction; Fantasy fiction; Romantic suspense fiction